SEASONAL VARIATION AND CLINICAL IMPACT OF ROTAVIRUS AND CO-INFECTING ENTERIC PATHOGENS IN CHILDHOOD DIARRHEA: INSIGHTS FROM A TERTIARY CARE HOSPITAL IN INDORE, MADHYA PRADESH - Mr. Ankur Vashishtha; Dr. Madhurendra Singh Rajput; Dr. Madhurendra Singh Rajput; Mr. Gautam Panwar; Dr. Navdeep; Mrs. Prigya Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background Diarrhea remains a leading cause of morbidity and mortality among children under five years of age, especially in developing countries. Rotavirus is a predominant etiological agent, often associated with co-infections from other enteric pathogens, complicating clinical outcomes. This study evaluates the seasonal variation and clinical impact of rotavirus and co-infecting enteric pathogens in childhood diarrhea cases at a tertiary care hospital in Indore, Madhya Pradesh. Methods A prospective observational study was conducted over 12 months, enrolling children under five presenting with acute diarrhea. Stool samples were collected and tested for rotavirus using enzyme-linked immunosorbent assay (ELISA). Additional enteric pathogens were identified using polymerase chain reaction (PCR) and culture methods. Data on clinical symptoms, treatment outcomes, and seasonal distribution were analyzed. Results Of the 500 children enrolled, 40% tested positive for rotavirus. Co-infections were observed in 35% of the rotavirus-positive cases, with enteric pathogens such as Escherichia coli, Shigella spp., and Giardia lamblia being the most common. A significant seasonal variation was noted, with peak incidence during the winter months (November-February). Children with co-infections had more severe clinical symptoms and longer hospital stays compared to those with rotavirus mono-infection. Conclusion Rotavirus remains a significant cause of childhood diarrhea in Indore, with a pronounced seasonal pattern. Co-infections with other enteric pathogens exacerbate disease severity, highlighting the need for comprehensive diagnostic and therapeutic approaches in managing childhood diarrhea.